Demographic differences in the treatment of unilateral vocal fold paralysis - Mit A. Patel; Jonathan M. Bock; Joel H. Blumin; David R. Friedland; Jazzmyne A. Adams; Ling Tong; Kristen I. Osinski; Jake Luo (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective To determine the impact of patient demographics and social determinants of health on treatment pathways for unilateral vocal fold paralysis (UVFP) at a tertiary laryngology clinic. Study design Retrospective medical record review. Methods Patient demographics (age, gender, race, ethnicity, and insurance status) were extracted for adults diagnosed with UVFP between 2009 and 2019. Odds ratios for the associations between sociodemographic factors and UVFP treatment pathways were determined by chi‐square analyses. Results A total of 1490 UVFP diagnoses were identified during the study period with the majority being female (58%), White (85%), non‐Hispanic (97%), and publicly insured (54%). Five treatment pathways were identified: observation, injection laryngoplasty, voice therapy, laryngeal framework surgery/thyroplasty, and reinnervation surgery. There were 538 patients who underwent observation, 512 injection laryngoplasty, 366 voice therapy, 136 thyroplasty, and 26 laryngeal reinnervation surgery. Males were more likely to undergo injection laryngoplasty than females (OR 1.32; CI 1.08–1.61), whereas females were more likely to undergo voice therapy (OR 1.39; CI 1.09–1.76). Patients with public insurance (OR 1.48; CI 1.03–2.14) and Hispanics (OR 2.60; CI 1.18–5.72) were more likely to undergo thyroplasty. Patients who underwent reinnervation surgery were younger than those in other treatment pathways (median: 39.1 years vs. 50.7–56.1 years). Conclusions Gender, ethnicity, and insurance status were significantly associated with specific UVFP treatment pathways. Patients with public insurance were more likely to undergo surgical intervention than voice therapy. This data overall supports differences in care pathway utilization for UVFP based on social determinants of health. Level of evidence Level IV.